Does supplier development lead to supplier satisfaction and relationship continuation?. Issue 3 (June 2019) - Glavee-Geo, Richard
Abstract: The primary purpose of this study is to find out if supplier development can serve as a means for buying firms to actively increase supplier satisfaction and eventually predict relationship continuity. Supplier relationships provide an essential means for buying firms to access and leverage supplier resources. One way in which buying firms influence the supply management process is through supplier development. The findings show that supplier development is an important means by which buying firms can increase supplier satisfaction. Supplier development significantly predicts the future of business relationships. Further analysis based on polynomial regressions provides evidence to show how congruence or discrepancy between economic and non-economic satisfaction impact continuance. Highlights: The paper provides insights into supplier development. It links supplier development to performance, satisfaction and relation continuity. Supplier development significantly predicts the relationship continuity expectation. Post-hoc analysis based on polynomial regressions provide further understanding of the issues under study.